Winged bean: A one stop supermarket - Kumar Soni, Jeetendra; Kumar Sunani, Sunil; Lungmuana; Shakuntala, I (Indian Horticulture, 2022)
Winged bean is high-yielding underutilized potential legume crop. It possesses high nutritious value and requires the least management practices. Apart from these benefits, the climatic condition of Mizoram are very well suitable for winged bean cultivation and blessed with rich diversity. In order to boost its production and alleviate the malnutrition problem of the state, it is important to go for scientific cultivation practices with selection of high yielding variety or local germplasm.